Low-Cost Honeycomb Biomass Adsorbent for Efficient Pt Recovery from Automobile Catalyst Waste - Rafał Olchowski; Patryk Szymczak; Ryszard Dobrowolski (Molecules)
Spent automobile catalysts can be an important source of platinum for industry applications. Low-cost and simple technologies for platinum recovery from this source are sought, especially involving the application of green adsorbents. Honeycomb biowaste can be an excellent candidate for this purpose; n-hexane-treated honeycomb biowaste is therefore obtained for the first time. This material is characterized using several instrumental techniques, confirming the presence of O, N, and P heteroatoms on its surface and the complex morphology of its particles. The maximum static Pt(II)/Pt(IV) adsorption (46 mg/g and 60 mg/g, respectively) onto the n-hexane-extracted honeycomb biomass is reached at pH = 1.55 and a contact time of 50 h. The adsorption kinetics are best fitted to the pseudo-second-order model in both cases. The Langmuir model best described the Pt(II)/Pt(IV) adsorption isotherms on the studied material. Quantitative desorption of the Pt from the studied material is reached for 1 mol/L thiourea dissolved in HCl. The adsorption mechanism of Pt(IV) ions onto the obtained material is based mainly on the surface complexation reactions. The studied material is successfully applied for the first time for Pt(IV) removal from a spent automobile catalyst leachate.